Arata Isozaki - Isozaki, Arata; Oshima, Ken Tadashi, 1965- (London : Phaidon, 2009)
This work presents the most comprehensive selection available of Arata Isozaki's built and unbuilt projects from the beginning of his career to the present day and is extensively illustrated with drawings, silkscreens, sketches and models from the Isozaki Office Archive.
Includes bibliographical references and index.
Keywords: Isozaki, Arata